Large Work Function Shift of Gold Induced by a Novel Perfluorinated Azobenzene‐Based Self‐Assembled Monolayer 1. (31st July 2012) - Crivillers, Núria; Osella, Silvio; Van Dyck, Colin; Lazzerini, Giovanni M.; Cornil, David; Liscio, Andrea; Di Stasio, Francesco; Mian, Shabbir; Fenwick, Oliver; Reinders, Federica; Neuburger, Markus; Treossi, Emanuele; et al.
<x xml:space="preserve">Abstract</x> Tune it with light! Self‐assembled monolayers on gold based on a chemisorbed novel azobenzene derivative with a perfluorinated terminal phenyl ring are prepared. The modified substrate shows a significant work function increase compared to the bare metal. The photo‐conversion between trans and cis isomers chemisorbed on the surface shows great perspectives for being an accessible route to tune the gold properties by means of light. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>